2020
DOI: 10.14701/ahbps.2020.24.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The role of down staging treatment in the management of locally advanced intrahepatic cholangiocarcinoma: Review of literature and pooled analysis

Abstract: Backgrounds/Aims: Approximately 60-80% of patients with intrahepatic cholangiocarcinoma (iCCA) are not suitable for surgical resection due to advanced disease at presentation. This review assesses the role of surgical resection followed by down staging treatment in the management of patients with locally advanced iCCA. Methods: A systematic review and pooled analysis were performed of the relevant published studies published between January 2000-December 2018. The primary outcome measure was overall survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The total number of patients receiving NAT was very low (6.7%). This is consistent with other published series, including case reports, retrospective analyses, systematic reviews, and meta-analyses, many of which were aimed at downstaging patients who were not initially resectable [ 24 , 36 , 37 ]. Data from our study support the idea that the use of NAT is limited to patients considered to be at high risks of recurrence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The total number of patients receiving NAT was very low (6.7%). This is consistent with other published series, including case reports, retrospective analyses, systematic reviews, and meta-analyses, many of which were aimed at downstaging patients who were not initially resectable [ 24 , 36 , 37 ]. Data from our study support the idea that the use of NAT is limited to patients considered to be at high risks of recurrence.…”
Section: Discussionsupporting
confidence: 91%
“…Available data on the use of NAT for ICC are limited and often extrapolated from studies utilizing NAT to downstage patients for surgical resection. Other data come from case reports, single institution studies, systematic reviews, or meta-analyses on ICC or from studies examining the utilization of NAT for other GI malignancies [ 24 , 36 , 37 ]. In this study, we queried the NCDB to examine the current use and associated outcomes of NAT for the treatment of resectable ICC.…”
Section: Discussionmentioning
confidence: 99%
“…In a large meta-analysis of 18 studies and 1,880 patients, including eight studies with chemotherapy. Patients who underwent resection following downstaging had significantly longer median survival compared with patients who did not (29 mo vs 12 mo, P < 0.001)[ 49 ]. In another systematic review of 132 patients, 27 patients (20.5%) were downstaged to surgical resection candidates[ 42 ].…”
Section: Evidence For Neoadjuvant Therapy In Iccmentioning
confidence: 99%
“…Regarding neoadjuvant chemotherapy, the evidence is even less persuasive, as there have been no prospective randomized trials assessing the value of neoadjuvant chemotherapy with ICC. A few retrospective studies, consisting of 1880 patients in total, have shown that neoadjuvant chemotherapy can down-stage unresectable ICC, and increase the proportion of patients eligible for surgery (38%, of them 60% R0 resections), in turn improving the outcomes of patients with ICC [ 73 ].…”
Section: Neoadjuvant and Adjuvant Therapymentioning
confidence: 99%